Study of the binary system fly ash/sugarcane bagasse ash (FA/SCBA) in SiO2/K2O alkali-activated binders - Castaldelli, V. N. [UNESP] (2016)
Due environmental problems related to Portland cement consumption, many studies have been performed to diminish its use. One solution is the development of alkali-activated binders, which can decrease CO2 emissions and energy consumption by 70% when compared to Portland cement production. In addition, an alkali-activated binder presents mechanical properties similar to Portland cement mixtures, which turns into an interesting material in civil construction. Aluminosilicate-based materials are important raw materials to produce the alkali-activated binders. Therefore, two residues are presented as an aluminosilicate source in this study: fly ash (FA) and sugarcane bagasse ash (SCBA). Both residues were obtained from a combustion process to generate energy, the former from coal and the latter from the bagasse of the sugarcane industry. In addition, the alkaline activating solution is an important factor to achieve improved mechanical properties. In this context, this study investigated the influence of four different SiO2/K2O molar ratios (0, 0.36, 0.75 and 1.22) in the activating solution with a constant water content, and three FA/SCBA binder proportions (75/25, 50/50 and 25/75). Microstructural characterization was carried out by X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy, mercury intrusion porosimetry, pH and electrical conductivity measurements to study the evolution of the reaction process. The compressive strength of mortars was assessed in order to determine the optimum SiO2/K2O molar ratio and FA/SCBA ratio. The tests showed that a SiO2/K2O molar ratio of 0.75 and FA/SCBA proportion of 75/25 provided the best mechanical properties.